Molecular Modelling of Oryza sativa Starch-branching Enzyme 1 - Mohammed, Sulaiman; Ndejiko, Mohammed Jibrin; Usman, Mohammed Maikudi; Kaya, Yilmaz; Huyop, Fahrul Zaman (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Starch-branching enzymes (SBE) serves as the only enzyme generating glucan branches in green plants and consequently plays a significant role on the resulting starch final structure. Research on rice (Oryza sativa) SBE1 (OsSBE1) structural biology remain untapped. Therefore, there is a necessity for research on the enzyme molecular structure which could lead to the protein function annotation, starch production and energy booster drug design. Analysis of OsSBE1 secondary structure, domains and their interactions, enzyme 3D structure prediction and validation based on C-score were carried out. The OsSBE1 primary sequence was retrieved from GenBank and its secondary structure was predicted to be; Î±-helix (27.68%), extended strand (22.78%) and higher random coil (949.54%). Enzyme domains were found to be carbohydrate-binding module (CBM) 48 (isoamylase N-terminal domain), Î±-amylase catalytic domain and Î±-amylase C-terminal all-beta domain with active sites important amino acids asparagine and glutamic acid. From the five 3D models generated, model 3 displayed best prediction. The Ramachandran refinement has 97.3 amino acids residues in favoured region and 0.4 C-score. This bioinformatics study has elucidated on the OsSBE1 molecular model and first to report on its domain interaction.